Network disruption detected in UY (Uruguay) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Uruguay. Data sourced from IODA.
Network Disruption Incident ID: UY-2026-0001. Severity: critical. Confidence: 70%